The Impact of Sleep Pattern in School/Work Performance During the COVID-19 Home Quarantine in Patients With Narcolepsy - Zhao, Mengke; Zhang, Baokun; Tang, Jiyou; Zhang, Xiao (Frontiers in Neurology, 2022)
Objectives Narcolepsy patients were observed improvements in their academic performance during the COVID-19 home quarantine. Therefore, we aim to investigate the influence of sleep behavioral changes on school/work performance in narcolepsy patients during the home quarantine. Methods Patients admitted to Shandong Provincial Qianfoshan Hospital from Jan 1, 2017 to Jan 1, 2021 who were diagnosed with narcolepsy were studied by online questionnaires in two different periods (during and 1 year after the COVID-19 home quarantine), including five aspects: (1) changes in school/work performance (percentile ranking in class/Sheehan Disability Scale 1, SDS1); (2) daytime functions; (3) clinical symptoms; (4) psychological moods; (5) medication situations. Results A total of 46 narcolepsy patients 34 (73.9%) narcolepsy type 1, 12 (26.1%) narcolepsy type 2 with average age of 20.76 ± 8.99 years and an equal number of age and gender matched control subjects were enrolled. During the COVID-19 home quarantine, the narcolepsy patients were found that they altered sleep patterns, including later get up time (P < 0.001), longer total sleep time (TST, P = 0.001), better sleep quality (PSQI, P = 0.001), and lower anxiety level (P = 0.005). Their school/work performance improved parallelly [with better percentile ranking (P = 0.001) and lower SDS1 scores (P = 0.002)]. The results of multiple linear stepwise regression analysis showed a linear regression relationship between TST [efficient (95%) −7.356 (−13.570 to 1.143)], SDS1 score [efficient (95%) 6.580 (2.346–10.815), P = 0.004] and the percentile ranking after adjusting for potential effects. Both the improvements of sleep behavior and school/work performance disappeared after the end of COVID-19 home quarantine. No similar fluctuation was found in the control group. Discussion Changes in sleep pattern during the COVID-19 home quarantine, such as longer sleep time and later wake-up time, can reduce the degree of daytime sleepiness and increase the degree of daytime wakefulness of narcolepsy patients, which can alleviate the impact of the disease on school/work performance.